Building the sex dungeon: Gay leather culture and the development of spaces for recreational sex at home. (2nd May 2022) - Cubbin, Tom
Abstract : This article examines the role of the gay leather community in the development of the home sex dungeon since the 1970s. The author maps points of contact between commercially produced equipment, publications containing advice on furnishing, and the approaches production of a domestic space that was documented by its owner. By tracing how style developed in tandem with collective making processes, the author reveals the centrality of collective making processes to the development of gay leather culture and identity in the United States. However, as the production of spaces for sexual fantasy have a limited space for expression in the home, the sex dungeon can also reveal tensions inherent in the construction of the leather identity.